Association of fibroblast growth factor-23 among chronic kidney disease patients with mineral bone disease - Toppo, Ashok K.; Toppo, Deepika; Minj, Dipti R.; Gupta, Rishabh (International Journal of Advances in Medicine, 2021)
Background: Chronic kidney disease (CKD) is characterized by slow and progressive loss of kidney function over years. Most of the time it goes undetected till severe irreparable damage has occurred. CKD is a worldwide public health problem. Methods: The present cross sectional study was conducted in nephrology outpatient department (OPD) and medicine wards of Government Medical College and Hospital, Ambikapur, Sarguja, Chhattisgarh, India from June 2020 to June 2021. The study involved 50 adult patients (>18 years) of CKD who were on hemodialysis. Patients who are not willing to participate and comatose patients were excluded from the study. Results: Among the CKD patients, 10 (20%) had left ventricular hypertrophy, 5 (10%) patients had left ventricular dysfunction with ejection fraction (EF) less than 40. 98% of the study participants were undergoing twice weekly hemodialysis and 2% were on thrice weekly hemodialysis. No significant association was found between left ventricular hypertrophy (LVH), pulmonary arterial hypertension (PAH), left ventricular dysfunction (LVD) with fibroblast growth factor-23 (FGF-23) (p>0.05) whereas there was a significant association between phosphate and FGF-23 (p<0.05) and between calcium and FGF-23 (p<0.05). Conclusions: CKD mineral and bone metabolism (MBD) is common in patients with CKD especially stage 5. They are also prone for cardiovascular manifestation. FGF23 levels were high in those with elevated phosphorous, left ventricular hypertrophy and left ventricular dysfunction. Levels of calcium, intact parathyroid hormone (iPTH) and ejection fraction did not correlate with FGF-23. Larger population in the study would have helped in actual identification of these patients and also helped in the knowing the predominant role of FGF-23.